2017
DOI: 10.1111/1365-2664.12979
|View full text |Cite
|
Sign up to set email alerts
|

Implications of plant functional traits and drought survival strategies for ecological restoration

Abstract: Restoration of degraded grasslands through active revegetation often involves re‐establishing populations of native grasses, which must withstand increasing drought stress to persist beyond initial establishment. In perennial species, superior dehydration tolerance is expected to result in more conservative growth, but this trade‐off has seldom been studied among populations of herbaceous species. We measured seasonal growth and foliar and root functional traits under non‐limiting water conditions, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 52 publications
5
28
1
Order By: Relevance
“…In agreement with Avolio and Smith (2013c), we found that drought selected genotypes G2 S and G11 S were more plastic in root:shoot allocation (although directionally opposite), which follows patterns of selection under drought in other species (Nicotra et al., 2010). G11 S in particular dedicated more resources to thick roots with greater RDMC, greater RDMC plasticity and lower specific root length consistent with tolerance phenotypes in other grasses (Balachowski & Volaire, 2018; Bristiel et al., 2019; de Vries et al., 2016). Overall differences between G2 S and G11 S raise the somewhat obvious but important insight of no single drought resistant phenotype.…”
Section: Discussionsupporting
confidence: 68%
“…In agreement with Avolio and Smith (2013c), we found that drought selected genotypes G2 S and G11 S were more plastic in root:shoot allocation (although directionally opposite), which follows patterns of selection under drought in other species (Nicotra et al., 2010). G11 S in particular dedicated more resources to thick roots with greater RDMC, greater RDMC plasticity and lower specific root length consistent with tolerance phenotypes in other grasses (Balachowski & Volaire, 2018; Bristiel et al., 2019; de Vries et al., 2016). Overall differences between G2 S and G11 S raise the somewhat obvious but important insight of no single drought resistant phenotype.…”
Section: Discussionsupporting
confidence: 68%
“…We utilized species from different families that are common in central coastal California and represent different life forms and combinations of traits: a grass species Elymus glaucus , a long‐lived perennial herbaceous forb E. latifolium , a semiwoody subshrub M. aurantiacus , and the woody shrub M. californica . Little is known of the photosynthetic physiology of these species, although there appear to be trade‐offs between resource acquisition and drought for E. glaucus (Balachowski & Volaire, ). Some life history trade‐offs might appear minor but cause important interactions with drought (Shriver, ).…”
Section: Discussionmentioning
confidence: 99%
“…Weaker relationships among grown ecotypes could also be due to maternal effects related to the agronomic environments in which seeds were produced rather than to home climate. Previous studies of perennial grass ecotypes across latitudinal gradients have similarly found trade‐offs between growth potential and drought resistance or drought resistance traits, including leaf width, WUE, leaf π o , and regrowth following drought (Aspinwall et al., 2013; Balachowski & Volaire, 2018; Bristiel et al., 2018; Bushey, 2017). Together with these studies, our results for leaf size and π o suggest that intraspecific growth versus drought resistance trade‐offs may involve a variety of drought resistance traits in perennial grasses.…”
Section: Discussionmentioning
confidence: 93%
“…Trade‐offs between growth and drought resistance are strong at broad taxonomic scales (Brodribb et al., 2007; Reich, 2014; Sack et al., 2013), but have also been observed within species (Balachowski & Volaire, 2018; Isaac‐Renton et al., 2018; Montwe et al., 2016). In E. elymoides , we found that more productive ecotypes had larger individual leaves and higher leaf π o , traits associated with lower dehydration tolerance (Bartlett, et al., 2012; Craine et al., 2013; Scoffoni et al., 2011).…”
Section: Discussionmentioning
confidence: 99%